Switching to ublituximab from prior anti-CD20 monoclonal antibody therapy: a case report series - Berkovich, Regina; Calkwood, Jonathan; Crayton, Heidi; Erwin, April; Faissner, Simon; Gold, Ralf; Katz, Joshua; Leekoff, Mark (Frontiers in Immunology, 2025)
IntroductionAnti-CD20 monoclonal antibody (mAb) therapies used to treat multiple sclerosis (MS) differ in their molecular structures, epitope recognition, and mechanisms of CD20-positive (CD20+) cell lysis, which may impact clinical efficacy and tolerability and support within-class switching for patients with suboptimal response to a prior anti-CD20 mAb.Patients and methodsThis is a retrospective case series of 7 individuals with MS treated in private practice or at an MS clinic who switched to ublituximab from a different anti-CD20 mAb therapy due to efficacy or tolerability concerns.Case descriptionsDetails of each case, including clinical and/or radiological outcomes on initial anti-CD20 mAb therapy, reasons for switching, and outcomes after starting ublituximab therapy are provided.DiscussionThese cases highlight suboptimal B-cell depletion, inadequate MS disease control, and/or tolerability concerns in people with MS who had clinical improvements or stabilization of disease following a switch from ocrelizumab or rituximab to ublituximab.ConclusionWithin-class switching from a prior anti-CD20 mAb therapy to ublituximab is feasible and may improve outcomes in some people with MS.